THE ROLE OF TREATMENT WITH HIGH-DOSE CORTICOSTEROIDS IN SEVERE LEPTOSPIROSIS WITH PULMONARY COMPLICATIONS - PARAMITHA, MARIA SATYA; SUTRISUNA; PUSPITASARI, MYRA (International Journal of Applied Pharmaceutics, 2019)
Objective: To investigate the effectiveness of high-dose corticosteroids in patients with severe leptospirosis, especially in reducing morbidity and mortality rates. Methods: Literature searches were conducted using PubMed® and SCOPUS®. One systematic review and one systematic review with meta-analysis were selected from three chosen studies. Results: The systematic review from Rodrigo et al. only included qualitative synthesis from four interventional studies. Early administration of methylprednisolone can be beneficial; however, low number and poor methodological quality of the studies question the validity of this review. Duggal et al. stated that there was no significant difference in the therapeutic effects of early high-dose corticosteroids (P ³ 0.05; 95% CI: 0.81–1.37), early low-dose corticosteroids (P ³ 0.05; 95% CI: 0.3–1.03), and late low-dose corticosteroids (P ³ 0.05; 95% CI: 0.11–2.52). Limited number of studies and high statistical heterogeneity, however, are major drawbacks for this review. Conclusion: Evidence about the role of high-dose corticosteroids in severe leptospirosis patients with pulmonary complications, especially their benefits, is still limited. Additional randomized, controlled trials with adequate statistical power still need to be conducted.